Climate forcing due to future ozone changes: an intercomparison of metrics and methods - W. J. Collins; F. M. O'Connor; F. M. O'Connor; R. E. Byrom; Ø. Hodnebrog; P. Jöckel; M. Mertens; M. Mertens; G. Myhre; M. Nützel; M. Nützel; D. Olivié; et al. (Atmospheric Chemistry and Physics)
This study assesses three different measures of radiative forcing (instantaneous: IRF; stratospheric-temperature adjusted: SARF; effective: ERF) for future changes in ozone. These use a combination of online and offline methods. We separate the effects of changes in ozone precursors and ozone-depleting substances (ODSs) and configure model experiments such that only ozone changes (including consequent changes in humidity, clouds and surface albedo) affect the evolution of the model physics and dynamics.